(3bUjOI aj GdVGO hGdXG eTJedI Ydi LejY eG aj GdbQBf hNdGa GdBFeI ajgGs - (3YR GdOjf CHh eMeO YHO GdQGRb Hf QRb Gddg Hf CHj HcQ Hf Nda GdQGTYfjs
(3ChdgG (B:s
(3bGd GdTjN GdQGTYfi gPg GdbUjOI ai GdVGO GdXG eTJedI Ydi LejY eG ai GdbQBf hNdGa GdCFeI ajgG MaXJ daXkG YXje GdhYX s
(3BNQgG (B:s
(3TYGY CfhGQgG jMci PcGA hjLdhG eGYdi GdbdH ef Tc hef ONf SejJgG OQI GdbGQF hfSHJgG HMQ GdHSjW bQjgG hGNJHQJjf JeJ HMeO Gddg hYhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG OYGA BNQ GdYGes
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(190) s
Keywords: (3GdeLGejYs